STRATEGI KOMUNIKASI SOSIAL BERBASIS NILAI ISLAM DALAM PEMBERDAYAAN PEREMPUAN: STUDI KASUS PIMPINAN WILAYAH WANITA ISLAM (PWWI) PROVINSI LAMPUNG - Ilah Hollah; Eneng Purwanti (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the social communication strategies implemented by the Lampung Province Women's Islamic Leadership (PWWI) in empowering women based on Islamic values. Amidst the challenges of modernization and shifting patterns of social interaction, religious-based women's organizations face demands to not only be a forum for religious study, but also a driving force for socio-economic independence. Using descriptive qualitative methods, this study collected data through in-depth interviews, participatory observation, and documentation of organizational activities. The results show that social communication in PWWI Lampung functions as a mechanism for social cohesion, which is operationalized through three main strategies: (1) Internalization of transformative Islamic values in da'wah activities, (2) Strengthening socioeconomic capital through MSME networks and halal certification, and (3) Adaptation of digital communication to expand the reach of public advocacy. This study concludes that the integration of spiritual values in social communication has proven effective in increasing member participation and shaping the collective identity of women who are empowered, independent, and responsive to contemporary social issues.